Social and ethnic inequalities in the offer and uptake of prenatal screening and diagnosis in the UK: a systematic review. - Rowe, R; Garcia, J; Davidson, L (2004)
OBJECTIVE: To review studies addressing the question of whether there are social inequalities in either the offer or the uptake of prenatal testing in the UK. METHOD: Systematic review of studies assessing the offer or uptake of prenatal screening or diagnosis according to social class or ethnic origin. Electronic databases were searched using a strategy developed for a review of inequalities in access to maternity care supplemented with terms specific to prenatal testing. Further papers were identified from reference lists, citation searches and key organizations. RESULTS: From over 600 identified papers, 41 were potentially relevant. Twenty met the inclusion criteria. The studies included covered screening and/or diagnosis for Down's syndrome, neural tube defects, haemoglobin disorders and HIV. Many studies were limited by small numbers or poor reporting of data and analysis. Six studies reported data on prenatal testing according to women's social class or educational level. None found any significant social inequalities in testing. Some studies suggested that women of South Asian origin might be up to 70% less likely to receive prenatal testing for haemoglobin disorders and Down's syndrome than White women. A small number of studies suggested that South Asian women might be less likely to be offered testing. CONCLUSIONS: This review provides some evidence of ethnic inequalities in access to prenatal testing. Further research is required to improve our understanding of why testing may not be offered, the reasons for failure to take up testing when offered, and to identify whether there are other social inequalities in access to prenatal testing.